2012
DOI: 10.1183/09031936.00186311
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-quantified emphysema distribution is associated with lung function decline

Abstract: Emphysema distribution is associated with chronic obstructive pulmonary disease. It is, however, unknown whether computed tomography (CT)-quantified emphysema distribution (upper/lower lobe) is associated with lung function decline in heavy (former) smokers.587 male participants underwent lung CT and pulmonary function testing at baseline and after a median (interquartile range) follow-up of 2.9 (2.8-3.0) yrs. The lungs were automatically segmented based on anatomically defined lung lobes. Severity of emphysem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…Th e fi ndings of this study are in keeping with another publication showing that in patients with a severe smoking history the subsequent emphysema is rather equally distributed between the upper and lower lung lobes (3). Th is article elucidates in detail the lung functional impact of the emphysema distribution with upper lobe distribution of emphysema being associated with a lower lung function.…”
Section: Lung Lobes Vs Halvessupporting
confidence: 71%
See 1 more Smart Citation
“…Th e fi ndings of this study are in keeping with another publication showing that in patients with a severe smoking history the subsequent emphysema is rather equally distributed between the upper and lower lung lobes (3). Th is article elucidates in detail the lung functional impact of the emphysema distribution with upper lobe distribution of emphysema being associated with a lower lung function.…”
Section: Lung Lobes Vs Halvessupporting
confidence: 71%
“…Th e defi nition of the leading component of the disease and further subclassifi cation of changes in these components by means of CT are termed CTphenotyping. A clear phenotypisation would enhance studies of pathophysiologic mechanisms and genetic determinants of the disease in terms of predisposition/ risk to develop the disease generally or a specifi c phenotype of the disease (3).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have suggested that emphysema distribution is independently associated with COPD progression. For instance, in one study upper-lobe predominant CT quantified emphysema was associated with more rapid decrease in lung function than lower-lobe predominant disease (27); and in another recent study, more homogenous emphysema distribution was associated with accelerated decline in lung function as compared to heterogenous disease (28). AAs may have less lower-lung emphysema because of genetic differences, such as α 1 anti-trypsin deficiency, which occurs at higher frequency among Whites of European descent (29).…”
Section: Discussionmentioning
confidence: 99%
“…The understanding that unique spatial patterns of emphysema serve as indicators of COPD subtypes has spawned progress in lobe segmentation algorithms 17, 18 as well as the need to evaluate CT-based features 19 . Although our understanding related to the clinical implications of the spatial patterns of emphysema is emerging 20 , little is understood about the non-emphysematous component of COPD, commonly associated with small airways disease.…”
Section: Introductionmentioning
confidence: 99%